Checklists of crustaceans of freshwater and marine fishes of Basrah Province, Iraq - Khamees, N.R.; Mhaisen, F.T.; Ali, A.H. (Mesopotamian Journal of Marine Sciences, 2022)
Reviewing the literature on all the crustaceans parasitizing freshwater and marine fishes of Basrah province, Iraq indicated the presence of 74 crustacean taxa. Sixty-five taxa belonged to the class Maxillopoda while nine taxa belonged to the class Malacostraca. All these crustaceans were adults living on the external surface of their fish hosts while three taxa were reported as larvae. Fifty-five species of such crustaceans were recorded from marine localities, 11 from freshwater localities and the remaining were from both freshwater and marine localities. The total number of crustacean species recorded for each fish host species fluctuated from a minimum of one crustacean species in 31 fish hosts to a maximum of 15 crustacean species in Chelon subviridis only. Number of fish hosts reported for these crustaceans fluctuated from one host in case of 45 crustacean species to a maximum of 18 hosts in case of praniza larvae of Gnathia sp.